Rhetoric and kairos : essays in history, theory, and praxis - Sipiora, Phillip; Baumlin, James S. (State University of New York Press, 2002)
This collection offers the first comprehensive discussion of the history, theory, and pedagogical applications of kairos, a seminal and recently revised concept of classical rhetoric. Augusto Rostagni, James L. Kinneavy, Richard Leo Enos, John Poulakos, a.